As sequências narrativas em sentença judicial - Cardoso, Valter Régis de Souza (2017)
In the present work, under the light of the Textual Discourse Analysis – approach developed by Adam (2011) – we propose to study the compositional structure of the genre judicial sentence, with a focus on the notion of text plan and on the narrative textual sequences that materialize in its report – part that contains a kind of synopsis of the process. With the main objective of analyzing how these sequences occur, we try to identify which textual and discursive elements are used in their structure, to describe these textual elements and their threads in the organization of narrative sequences, besides to interpret the function of these textual sequences for structuring and composition. In a broader sense, this research is grounded on the general propositions of the Text Linguistics in authors like Koch (1997; 1999; 2002; 2004), Koch e Elias (2012; 2013), Marcuschi (2002; 2008; 2012) among others. The corpus of this research is composed of a single sentence of a criminal nature, extracted from the Sentence Database of the Federal Justice of Rio Grande do Norte (JFRN) website. Regarding the applied methodology, the present research is of documental nature, whilst guided by an inductive-deductive reasoning and being of a qualitative and descriptive character. Methodologically, this research presents a documentary aspect and is guided by the methods of inductive and deductive reasoning, presenting a qualitative and descriptive character. Results indicate that the sentence report does not limit itself only to the listing and enumerating of the actions put into practice by the concerned parties throughout the legal process, but that it possess a high level of narrativization, displaying all components of a narrative sequence. And, because of the narratives at the global level, there are the smaller narratives, the so-called embedded narratives, which play an important contextualization and detailing mechanism of reported actions.